Current food labelling practices in online supermarkets in Australia - Maganja, Damian; Davies, Tazman; Sanavio, Laura; Louie, Jimmy C. Y.; Huffman, Mark D.; Trieu, Kathy; Wu, Jason H. Y. (The international journal of behavioral nutrition and physical activity, 2023)
Background Food product labelling can support consumer decision-making. Several food product labels (nutrition information panels (NIPs), ingredients lists, allergen declarations and country-of-origin) are mandated for physical product packaging in Australia, with a voluntary front-of-pack nutrition labelling system, Health Star Ratings (HSRs), also available. However, labelling requirements are not explicitly extended to online settings and the extent to which this information is available in these increasingly important food environments has not been assessed. Methods Data from all individual food product pages was collected from the online stores of the two dominant supermarket retailers in Australia using automated web scraping in April–May 2022 ( n = 22,077 products collected). We assessed the proportion of pages displaying NIPs, ingredients, allergens, country-of-origin and HSRs after excluding products ineligible to display the respective label. We also assessed whether HSRs were differentially available for higher- (healthier) and lower-scoring (less healthy) products, with HSR scores drawn from a comprehensive Australian food composition database, FoodSwitch. A manual inspection of randomly selected product pages ( n = 100 for each label type per supermarket), drawn from products displaying the relevant label, was conducted to assess whether the labels were immediately visible to users (i.e. without scrolling or clicking). Differences in labelling prevalence and visibility were compared using chi-squared tests. Results Across both supermarkets, country-of-origin labelling was almost complete (displayed on 93% of food product pages), but NIPs (49%), ingredients (34%) and allergens (53%) were less frequently displayed. HSRs were infrequently displayed (14% across both supermarkets) and more likely to be applied to higher-scoring products (22% on products with ≥ 3.5HSR v 0.4% on products with < 3.5HSR, p < 0.001). One supermarket was far more likely to make NIPs (100% v 2%, p < 0.001), ingredients (100% v 19%, p < 0.001) and allergens (97% v 0%, p < 0.001) information immediately visible, though the other made HSRs more apparent (22% v 75%, p < 0.001). Both supermarkets displayed country-of-origin labels prominently (100% v 86%, p < 0.001). Conclusions Food product labelling varies in online supermarkets in Australia overall and between supermarkets, while the design of online stores resulted in differences in labelling visibility. The near-complete display of country-of-origin labels and differential application of HSRs to higher-scoring products may reflect their use as marketing tools. Our findings highlight an urgent need for food labelling regulations to be updated to better account for online retail food environments.